Synthesis and Characterization of Zinc Oxide Nanoparticles (ZnO NPs) in Powder and in Thin Film using Corn Husk Extract via Green Chemistry. (2020) - Bakayoko, M.; Fall, A.; Ngom, I.; Sackey, J.; Ngom, B.D.; Tall, P.D.; Maaza, M.
Abstract: In this study, zinc oxide nanoparticles (ZnO NPs) in powder and in thin film were successfully synthesized first time using an eco-friendly, simple and cost effective green synthesis method mediated by corn husk (Zea mays) extract as an effective chelating agent, and zinc nitrate hexahydrate as precursor. Diverse characterizations techniques such as High Resolution – Scanning Electron Microscopy (HR-SEM), Energy Dispersive X- rays Spectroscopy (EDS), X-Rays Diffraction (XRD), and UV – Vis – NIR spectroscopy as well as Photoluminescence (PL) were investigated to confirm ZnO NPs nature. For the ZnO NPs powder, highly crystalline ZnO nanoparticles (ZnO NPs) annealed at 500°C which are 48.635 nm in particles size were characterised by HR-SEM and XRD analysis. The structure morphology and the constituents of the resultant ZnO powder were investigated respectively by HR-SEM and EDS. UV – Visible spectroscopy analysis was investigated on the optical band gap of ZnO NPs, which was calculated to be 3.31 eV. This result indicates that ZnO NPs can be used in metal oxide semiconductor-based devices. For the ZnO NPs thin film, XRD patterns of hexagonal wurtzite structure with c/a ratio about of 1.60 and μ – parameter of 0.38 were obtained. PL measurements showed a broad emission band in the 380 – 800 nm range, centred at 481 nm. ZnO NPs thin film yielded relatively more intense photoluminescence spectra than the ZnO NPs powder. The intrinsic point defects and defect level transitions responsible for the broad emission are discussed.